CLASSROOM INTERACTION ANALYSIS IN INDONESIAN EFL SPEAKING CLASS - Sinta Hoerun Nisa (University of Kuningan, 2014)
Abstract:Â This study entitles â€œClassroom Interaction Analysis in the EFL Speaking Classâ€ aimed at analyzing the categories of teacher talk, student talk and classroom interaction types used during EFL speaking class. The research employed a qualitative design and applied a case study. Subjects of the research were an English teacher and 25 students at the second semester of English Education Department of the University of Kuningan. The data were gained through naturalistic observation and document analysis. The data were analyzed by using FLINT (Foreign Language Interaction) system as developed by Moskowitz (1971) and types of classroom interaction of Malamah-Thomasâ€™ (1987) frameworks. The findings revealed that both teacher and students applied all categories of talk as mentioned in FLINT system and classroom interaction types. It is recommended for the teacher to apply more categories of â€˜praises and encouragesâ€™ to build studentsâ€™ confidence in speaking, â€˜asks questionsâ€™ to promote their communicative skill and to encourage students to use English during speaking activities, particularly in group work activities.Keywords: Classroom interaction, FLINT analysis, EFL speaking class.